From Cash to Deposits: Effects on Women’s Status andWell-being - Marquez-Padilla, Fernanda; Parker, Susan W. (Pontificia Universidad Católica del Perú, 2024)
We study the short term effects of an experiment which transitioned conditional cash transfer beneficiaries from receiving benefits in cash at temporary payment modules to receiving benefits through account deposits on women’s status, work and financial inclusion. The experiment was implemented in the context of the Mexican Prospera program in 150 communities in the state of Hidalgo. Our results suggest an immediate and important positive impact of the transition to deposits on women’s control of resources in the household.
Keywords: Conditional cash transfers; Financial inclusion; Women’s empowerment; Account deposits; Conditional cash transfers; Financial inclusion; Women’s empowerment; Account deposits; https://purl.org/pe-repo/ocde/ford#5.02.01